Effectiveness of an asthma integrated care program on asthma control and adherence to inhaled corticosteroids. (August 2015) - Guénette, Line; Breton, Marie-Claude; Grégoire, Jean-Pierre; Jobin, Marie-Sophie; Bolduc, Yves; Boulet, Louis-Philippe; Dorval, Eileen; Moisan, Jocelyne
Abstract Objective: To measure the effectiveness of an integrated care program for individuals with asthma aged 12–45 years, on asthma control and adherence to inhaled corticosteroids (ICS). Methods: Researchers used a theoretical model to develop the program and assessed effectiveness at 12 months, using a pragmatic controlled clinical trial design. Forty-two community pharmacists in Quebec, Canada recruited participants with either uncontrolled or mild-to-severe asthma. One group was exposed to the program; another received usual care. Asthma control was measured with the Asthma Control Questionnaire; ICS adherence was assessed with the Morisky medication adherence scale and the medication possession ratio. Program effectiveness was assessed with an intention-to-treat approach using multivariate generalized estimating equation models. Results: Among 108 exposed and 241 non-exposed, 52.2% had controlled asthma at baseline. At 12-months, asthma control had improved in both groups but the interaction between study groups and time was not significant (p = 0.09). The proportion of participants with good ICS adherence was low at baseline. Exposed participants showed improvement in adherence and the interaction between study groups and time was significant (p = 0.02). Conclusion: An integrated intervention, with healthcare professionals collaborating to optimize asthma control, can improve ICS adherence.